2014
DOI: 10.1136/gutjnl-2013-305806
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA profile study reveals a three-lncRNA signature associated with the survival of patients with oesophageal squamous cell carcinoma

Abstract: BackgroundOesophageal cancer is one of the most deadly forms of cancer worldwide. Long non-coding RNAs (lncRNAs) are often found to have important regulatory roles.ObjectiveTo assess the lncRNA expression profile of oesophageal squamous cell carcinoma (OSCC) and identify prognosis-related lncRNAs.MethodLncRNA expression profiles were studied by microarray in paired tumour and normal tissues from 119 patients with OSCC and validated by qRT-PCR. The 119 patients were divided randomly into training (n=60) and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
352
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 374 publications
(360 citation statements)
references
References 34 publications
6
352
1
1
Order By: Relevance
“…Four public esophageal cancer microarray profiling datasets (GSE45670,23 GSE53622,12 GSE89102, GSE92396) were downloaded from the Gene Expression Omnibus (GEO). lncRNAs profiling of GEO microarray datasets was annotated and analyzed based on the Affymetrix Human Genome U133 Plus 2.0 Array and U133A Array, Agilent‐038314 CBC Homo sapiens lncRNA + mRNA microarray V2.0, Agilent‐045997 Arraystar human lncRNA microarray V3, and Affymetrix Human Gene 1.0 ST Array platforms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four public esophageal cancer microarray profiling datasets (GSE45670,23 GSE53622,12 GSE89102, GSE92396) were downloaded from the Gene Expression Omnibus (GEO). lncRNAs profiling of GEO microarray datasets was annotated and analyzed based on the Affymetrix Human Genome U133 Plus 2.0 Array and U133A Array, Agilent‐038314 CBC Homo sapiens lncRNA + mRNA microarray V2.0, Agilent‐045997 Arraystar human lncRNA microarray V3, and Affymetrix Human Gene 1.0 ST Array platforms.…”
Section: Methodsmentioning
confidence: 99%
“…To date, increasing evidence have demonstrated that lncRNAs are widely expressed in most of organ tissues, and participate in various cellular biological process, including X chromatin imprinting, muscle cells differentiation, immune response, cell fate decision, tumor cell proliferation, and drug resistance 10, 11. Importantly, RNA sequencing and microarray analyses of tumor and normal tissues in diverse types of human cancers revealed that thousands of lncRNAs are dysregulated in cancer tissues, and part of these lncRNAs are emerging as key molecules during carcinogenesis 12, 13. lncRNAs involve in the tumorigenesis by functioning as oncogenes or tumor suppressors through chromatin remodeling, histone modification, acting as sponge for microRNAs, and affecting RNA stability 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence has demonstrated that lncRNAs exhibit crucial regulatory roles in the biological processes of cancer, including genomic imprinting, chromatin modification and post-transcriptional processing (7)(8)(9)(10). Increasingly, studies have indicated that lncRNAs may be used as potential prognostic biomarkers and therapeutic targets (11,12). Gastric adenocarcinoma-associated, positive CD44 regulator, long intergenic noncoding RNA (GAPLINC) has been demonstrated to be aberrantly expressed in gastric and colorectal cancer (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the function of uc009yby.1 in renal cells was investigated using two siRNAs to inhibit uc009yby.1 expression, revealing that this lncRNA could enhance renal cell proliferation; this suggests that uc009yby.1 may be a novel therapeutic target for ccRCC. Numerous studies have indicated that certain lncRNAs have aberrant expression profiles in various kinds of tumors, such as gastric (15)(16)(17), colon (18,19), esophageal (20)(21)(22) and liver (23) cancers. Yu et al (12) recently reported on a class of lncRNAs that are aberrantly expressed in ccRCC cells, in which multiple lncRNAs were upregulated.…”
Section: Discussionmentioning
confidence: 99%